2020
DOI: 10.3389/fphar.2020.603575
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effects of St. John’s Wort Extract Against Inflammatory and Oxidative Stress and in the Phagocytic and Migratory Activity of Mouse SIM-A9 Microglia

Abstract: Introduction: Herbal medicinal plants as Hypericum perforatum L., known as St. John’s wort (SJW) have been in use for a long time. SJW that is specifically used for the treatment of depressive disorders. Inflammatory cytokines derived from microglia play an important role in the regulation of the synthesis and reuptake of glutamate and influence synaptic function, morphology and neuronal plasticity. The present study was performed to investigate, whether STW3-VI, a special SJW extract has protective effects on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…In addition, we utilized the murine brain-derived microglia cell line SIM-A9 [ 48 ], which has been used in several studies of LPS-induced inflammation [ 49 , 50 , 51 ]. While the SIM-A9 cell line is an important model for microglia, it is a cell line (as compared to primary microglia) derived from the brain (not from the retina), and is of a different species than the RPE cells used in this study (murine vs. porcine).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we utilized the murine brain-derived microglia cell line SIM-A9 [ 48 ], which has been used in several studies of LPS-induced inflammation [ 49 , 50 , 51 ]. While the SIM-A9 cell line is an important model for microglia, it is a cell line (as compared to primary microglia) derived from the brain (not from the retina), and is of a different species than the RPE cells used in this study (murine vs. porcine).…”
Section: Discussionmentioning
confidence: 99%
“…Emodin is one of the active chemical constituents of Hypericum perforatum . Previous studies have shown that emodin can protect the brain from the excitatory toxicity of glutamate by reducing its release ( Bonaterra et al, 2020 ). Emodin has recently been reported to oppose chronic, unpredictable, mild stress-induced depressive-like behavior in mice by upregulating the levels of hippocampal glucocorticoid receptor and BDNF ( Li M. et al, 2014 ).…”
Section: Molecular Mechanism Of Action Of Sg Antidepressantsmentioning
confidence: 99%